Financial Inclusion, Poverty, and Income Inequality: Evidence from European Countries - Tsouli, Driss (Ekonomika, 2022)
This study contributes to the existing literature on financial inclusion by examining the determinants of financial inclusion and studying the impact of financial inclusion on poverty reduction and income inequality in European countries. We investigate the impact of financial inclusion on poverty and income inequality in 30 European countries during 2004-2019 based on a composite financial inclusion index (FII) constructed by using principal component analysis (PCA). Then we assess the impact of financial inclusion, on poverty and income inequality, by employing the fixed effect method. The estimates reveal that, for the European countries, GNI per capita, population density, inflation, and internet users have a positive and significant impact on financial inclusion across all the regressions. Rule of law has a positive impact on financial inclusion, and the age dependency ratio has a negative impact on financial inclusion. The findings also indicate that financial inclusion is significantly correlated with lower poverty for the full sample. Lastly, the present study supports the role of financial inclusion in reducing income inequality in European countries.